2009
DOI: 10.1002/humu.21126
|View full text |Cite
|
Sign up to set email alerts
|

Congenital disorders of glycosylation: an update on defects affecting the biosynthesis of dolichol-linked oligosaccharides

Abstract: Defects in the biosynthesis of the oligosaccharide precursor for N-glycosylation lead to decreased occupancy of glycosylation sites and thereby to diseases known as congenital disorders of glycosylation (CDG). In the last 20 years, approximately 1,000 CDG patients have been identified presenting with multiple organ dysfunctions. This review sets the state of the art by listing all mutations identified in the 15 genes (PMM2, MPI, DPAGT1, ALG1, ALG2, ALG3, ALG9, ALG12, ALG6, ALG8, DOLK, DPM1, DPM3, MPDU1, and RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
133
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 122 publications
(228 reference statements)
0
133
0
2
Order By: Relevance
“…It was first reported in 1998 (Burda et al 1998;K€ orner et al 1998) and about 37 patients have been described (Imbach et al 1999Gr€ unewald et al 2000;Hanefeld et al 2000;Westphal et al 2000aWestphal et al , b, 2003de Lonlay et al 2001;Schollen et al 2002;Newell et al 2003;Sun et al 2005;Vuillaumier-Barrot 2005;Eklund et al 2006;Haeuptle and Hennet 2009;Al-Owain et al 2010). The clinical presentation is mainly characterized by feeding problems and a moderately pronounced neurological disorder with psychomotor retardation, hypotonia, epilepsy, and internal strabismus Newell et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first reported in 1998 (Burda et al 1998;K€ orner et al 1998) and about 37 patients have been described (Imbach et al 1999Gr€ unewald et al 2000;Hanefeld et al 2000;Westphal et al 2000aWestphal et al , b, 2003de Lonlay et al 2001;Schollen et al 2002;Newell et al 2003;Sun et al 2005;Vuillaumier-Barrot 2005;Eklund et al 2006;Haeuptle and Hennet 2009;Al-Owain et al 2010). The clinical presentation is mainly characterized by feeding problems and a moderately pronounced neurological disorder with psychomotor retardation, hypotonia, epilepsy, and internal strabismus Newell et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes clinical and molecular findings in ten ALG6-CDG patients reported since 1998. Twenty-one different mutations have been described but the majority of patients have the c.998C>T (p.A333V) mutation, either in a compound heterozygous or homozygous state (Imbach et al 1999Gr€ unewald et al 2000;Hanefeld et al 2000;Westphal et al 2000aWestphal et al , b, 2003de Lonlay et al 2001;Schollen et al 2002;Newell et al 2003;Sun et al 2005;Vuillaumier-Barrot 2005;Eklund et al 2006;Haeuptle and Hennet 2009;Al-Owain et al 2010). Haeuptle and Hennet (2009) reported that most of the mutations affect amino acids positioned within the 11 TM domains, which compromise the integrity of the protein structure and alter the properties responsible for the binding of dolichol-linked glycans.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of the LLO Dol-PPGlcNAc 2 Man 5 is also typically found in cases of RFT1 deficiency [33,34]. Mutations in the MPDU1 and RTF1 genes yield forms of CDG with clinical features similar to those encountered in other types of defective LLO assembly [7].…”
Section: Defects Of Lipid-linked Oligosaccharide Biosynthesismentioning
confidence: 91%
“…Mutations in the phosphomannomutase-2 (PMM2, OMIM ID: 601785) gene represent by far the most frequent type of CDG, with an incidence of about 1 to 50'000. To date, more than 100 mutations in the PMM2 gene have been described [7]. Interestingly, the R141H mutation, which is the most common mutation by far, is found in 1 out of 80 individuals in most human populations [8].…”
Section: Phosphomannomutasementioning
confidence: 99%
See 1 more Smart Citation